Constrictive pericarditis in a patient with fiberglass lung disease: a case report - Chan-Yang Hsu; Hsin-Yi Chen; Min-Shiau Hsieh; Yi-Hsin Lee; Chou-Chin Lan; Mei-Chen Yang (BMC Pulmonary Medicine, 2024)
Abstract Background Fiberglass has a larger aerodynamic diameter and is less likely to be inhaled into the lungs. Further, it will be cleared even if it is mechanically broken into smaller pieces and inhaled into the lungs. Fiberglass lung disease has been well documented if long term exposure but was thought reversible and would not cause severe diseases. The diagnosis of fiberglass lung disease depends on exposure history and histopathological findings. However, the exact occupational exposure history is often difficult to identify because mixed substance exposure often occurs and fiberglass disease is not as well-known as asbestosis. Case presentation A 66-year-old man had unexplained transudative pericardial effusion requiring pleural pericardial window operation twice at another medical center where asbestosis was told because of his self-reported long-term asbestosis exposure and the histopathological finding of a ferruginous body in his lung. Constrictive pericarditis developed two years later and resulted in congestive heart failure. Radical pericardiectomy combined with lung biopsy was performed following chest computed tomography imaging and the transudative nature of pericardial effusion not compatible with asbestosis. However, the histopathologic findings of his lung and pericardium at our hospital only showed chronic fibrosis without any asbestosis body. The patient’s lung was found to be extremely fragile during a lung biopsy; histopathologic specimens were reviewed, and various fragments of fiberglass were found in the lung and pericardium. The patient’s occupational exposure was carefully reevaluated, and he restated that he was only exposed to asbestosis for 1–2 years but was heavily exposed to fiberglass for more than 40 years. This misleading exposure history was mainly because he was only familiar with the dangers of asbestos. Since most fiberglass lung diseases are reversible and the symptoms of heart failure resolve soon after surgery, only observation was needed. Ten months after radical pericardiectomy, his symptoms, pleural effusion, and impaired pulmonary function eventually resolved. Conclusion Fiberglass could cause inflammation of the pericardium, resulting in pericardial effusion and constrictive pericarditis, which could be severe and require radical pericardiectomy. Exact exposure history and histopathological examinations are the key to diagnosis.